Exploring Wordwall.Net Implementation in Vocabulary Learning at Junior High School - Roviani, Roviani; Mobit, Mobit; Srisudarso, Mansyur (IKIP Siliwangi, 2025)
This study explores the implementation of Wordwall.net in vocabulary learning for junior high school students. Vocabulary is fundamental in language acquisition, but traditional methods often fail to engage students, leading to poor outcomes. This research employs a qualitative case study approach to examine how Wordwall.net enhances vocabulary learning by making the process more interactive and enjoyable. Conducted in a junior high school in Karawang, the study involved four grade VIII students and used interviews, observations, and document analysis as data collection methods. The findings reveal that Wordwall.net significantly improves student engagement and vocabulary retention. Teachers played a crucial role in selecting appropriate activities, preparing lessons, and addressing challenges post-learning. Students responded positively to the platform, citing increased interaction, ease of use, and a more enjoyable learning experience. Despite its advantages, challenges remain, including the need for appropriate selection criteria and effective post-learning reinforcement. The study concludes that Wordwall.net is an effective tool in enhancing vocabulary learning, fostering a more dynamic and interactive classroom environment. Additionally, it highlights the importance of ongoing teacher support and training to maximize the platform's potential and address any limitations that may arise during its use, particularly in different educational contexts.